SELF-HARM DALAM AL-QUR’AN: Analisis Tematik Kata Bakhi dan Zhalama Nafs dalam Tafsir Al-Azhar - A'yun, Putri Qurrota (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Self-harm has been discussed as one of the crucial phenomena until now, and has become one of the objects of study from various fields. However, studies that examine this phenomenon from a Qur’anic perspective remain relatively limited. This research aims to analyze the concept of self-harm in the Qur’an through a thematic study of the terms ba>khi‘ and z}alama nafs, with reference to Buya Hamka’s Tafsir Al-Azhar. This study employs a library research method using a qualitative-descriptive approach. The data are analyzed by examining Qur’anic verses that contain these terms and interpreting them based on Buya Hamka’s exegetical explanations. The findings indicate that the Qur’anic concept of self-harm encompasses a broader scope of meaning than that offered by psychological definitions. The term ba>khi‘ describes an intense emotional impulse that may give rise to the desire to harm oneself, yet does not culminate in actual behavior. Meanwhile, z}alama nafs represents moral and spiritual forms of self-harm, such as arrogance, ingratitude for God’s blessings, and violations of religious values. According to Buya Hamka, although such actions constitute self-oppression, individuals who engage in them remain eligible for repentance and divine forgiveness.